IMPLEMENTING SSS (START WITH SIMPLE STORIES) METHOD TO IMPROVE STUDENTS’ READING COMPREHENSION IN EXTENSIVE READING ACTIVITY - Dian Arsitades Wiranegara (Journal of English for Academic and Specific Purposes (JEASP), 2022)
This paper is intended to present the idea of applying the SSS METHOD or stand for Start with Simple Stories extensive reading to improve reading comprehension of the lower achieving students. This can be a challenging task for teachers whose aims are to improve the students’ reading habit by providing them with a very conducive atmosphere of reading, involving and facilitating them in various reading activities with the reading material. Hence, the subjects of the research were the first year or freshmen students of senior high school. Two classes were assigned as the control and the experimental groups. The control group was taught reading comprehension by using the conventional way; while the experimental 1group 1was 1taught reading by using the SSS METHOD extensive reading. As the treatment conducted, both groups were given posttest. The 1result 1of the 1study has showed that 1there 1was 1a1significant1difference1in1the 1students’ 1reading comprehension 1achievement. The 1students in 1the experimental group significantly obtained higher scores than the ones in the control 1group.